Dynamic modeling and load transfer prediction of drill-string axial vibration in horizontal well drilling. (January 2023) - Liu, Weili; Ni, Hongjian; Wang, Yun; Guo, Yong; Gao, Yu; He, Peiyu
Abstract: A three-dimensional finite element dynamics model of drill-string is established considering dynamic friction model and buckling effect. The modified dynamics model is proved to have higher computational accuracy by laboratory experiment. A parameters study is conducted based on the dynamics model. Results show that the exciting force amplitude, drilling fluid density, axial force, friction coefficient, and drill-string dimension have significant effects on the friction reduction performance and effective propagation distance of axial vibration. A prediction model for vibration propagation distance is established, which facilitates efficient optimization of the axial vibration parameters in horizontal well drilling. This study can provide theoretical guidance for axial vibration to safely and efficiently reduce the sliding friction in exploitation of unconventional oil-gas reservoirs. Graphical Abstract: ga1 Highlights: A three-dimensional finite element dynamics model of drill-string is established considering the dynamic friction model and buckling effect. The modified dynamics model is proved to have higher computational accuracy by laboratory experiment. The main controlling factors affecting the sliding force and vibration load transfer are identified. A prediction model for vibration propagation distance is established, which facilitates efficient optimization of the axial vibration parameters.